Application Design Implementation Scheduling Overhaul Production Machinery At PT Semen Indonesia (Persero) Tbk. - Atmaningtyas, Linggar; Setyawan, Henry; Wahyuningtyas, Nunuk (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2020)
PT Semen Indonesia in its production, has a variety of machines that each day will perform a poction. With the continuous machine performance of PT Semen Indonesia will do the Overhaul of the machine owned. For now in the stage of scheduling Overhaul conducted by the company is still in a stage that lacks support because the software used can not update directly with SAP and still use Excel. In scheduling using SAP there is an issue where Software cannot determine the number of days present in the scheduling, unable to determine Shift, without filling in the PIC field and the Vendor Activity field keep running following Shift. The impact of the problem is that the process is disadvantaged at the time of the report generation and the lack of information. With such problems the company wants to create and implement a system scheduling Overhaul production machines. In the system can determine the number of days, can determine the Shift and also application demands to provide information at the time of the report generation.                Based on the test results of the Overhaul scheduling application with the Staff Department Of ICT and Staff Management Service Development, the results of the system can be easier to determine the number of days and Shift and the system can determine The selected vendor.Keyword: Website, Scheduling, production machinery, overhauls.